The Role of Tissue Engineering in Achilles Tendon Repair: A Review - Sahni, Varun; Tibrewal, Saket; Bissell, Lianne; S. Khan, Wasim (Current Stem Cell Research & Therapy, 2015)
Achilles tendon injuries are common but complex in nature. Healing occurs via scar tissue formation leading to poor patient outcomes. Currently surgical and non-surgical treatment leads to suboptimal tendon healing and has complications. Tissue engineering is an advancing field that can either augment surgical repair or provide an alternative method for Achilles tendon repair. This article will explore the principles behind tissue engineering in Achilles tendon repair. Furthermore it will describe the current literature regarding the different types of stem cells used in Achilles tendon repair, how different growth factors augment tendon repair, as well as the role of biomaterials in tissue engineering.
Keywords: stem cells